Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A=\(\frac{1}{1^2}\)+\(\frac{1}{2^2}\)+\(\frac{1}{3^2}\)+...+\(\frac{1}{50^2}\)
A=1+\(\frac{1}{2^2}\)\(\frac{1}{3^2}\)+...+\(\frac{1}{50^2}\)
A<1+\(\frac{1}{1\cdot2}\)+\(\frac{1}{2\cdot3}\)+...+\(\frac{1}{49\cdot50}\)
A<1+1-\(\frac{1}{2}\)+\(\frac{1}{2}\)-\(\frac{1}{3}\)+...+\(\frac{1}{49}\)-\(\frac{1}{50}\)
A<2-\(\frac{1}{50}\)<2
=>A<1(câu 1)
Câu 1:
\(A=\frac{1}{1^2}+\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+.....+\frac{1}{50^2}\)
\(A=\frac{1}{1\times1}+\frac{1}{2\times2}+\frac{1}{3\times3}+\frac{1}{4\times4}+.....+\frac{1}{50\times50}\)
\(A< \frac{1}{1\times1}+\frac{1}{1\times2}+\frac{1}{2\times3}+\frac{1}{3\times4}+.....+\frac{1}{49\times50}\)
\(A< 1+\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+.....+\frac{1}{49}-\frac{1}{50}\)
\(A< 2-\frac{1}{50}< 2\)
Câu 2:
\(S=3+\frac{3}{2}+\frac{3}{2^2}+.....+\frac{3}{2^9}\)
\(2S=6+3+\frac{3}{2}+.....+\frac{3}{2^8}\)
\(2S-S=\left(6+3+\frac{3}{2}+.....+\frac{3}{2^8}\right)-\left(3+\frac{3}{2}+\frac{3}{2^2}+.....+\frac{3}{2^9}\right)\)
\(S=6-\frac{3}{2^9}\)
\(S=\frac{3069}{512}\)
Câu 3:
\(\frac{1}{2\times3}=\frac{1}{6}\)
\(\frac{1}{2}-\frac{1}{3}=\frac{3}{6}-\frac{2}{6}=\frac{1}{6}\)
\(\Rightarrow\frac{1}{2\times3}=\frac{1}{2}-\frac{1}{3}\)
Câu 4:
\(M=\frac{9}{40}-\frac{11}{60}+\frac{13}{84}-\frac{15}{112}\)
\(M=\left(\frac{9}{40}-\frac{11}{60}\right)+\left(\frac{13}{84}-\frac{15}{112}\right)\)
\(M=\left(\frac{27}{120}-\frac{22}{120}\right)+\left(\frac{52}{336}-\frac{45}{336}\right)\)
\(M=\frac{1}{24}+\frac{1}{48}\)
\(M=\frac{2+1}{48}\)
\(M=\frac{3}{48}\)
\(M=\frac{1}{16}\)
Chúc bạn học tốt
câu 2:
s= 3+3/2+3/3^2+.....+3/2^9
=> 2s=6+3+3/2+...+3/2^8
=> 2s-s =( 6+3+3/2 + ....+3/2^8)- ( 3+3/2 +3/2^2+...+3/2^9)
=> s=6-3/2^9=3069/512
có:
(1994-1)+1=1994
Tổng là:
1994x(1994+1):2=1989015
Đáp số:1989015
1+2=(1+2)*2/2=>3/(1+2)=(3*2)/(1+2)*2=6/(2*3)
1+2+3=(1+3)*3/2=>3/(1+2+3)=6/(3*4)
........................
1+2+...+100=(1+100)*100/2=>3/(1+2+3+...+100)=6/(100*101)
=>A=6/(2*3)+6/(3*4)+...+6/(100*101)=6*(1/2-1/3+1/3-1/4+...+1/100-1/101)
=6*(1/2-1/101)=6*99/202=297/101
S = 1 + 2 + 22 + ... + 29 + 210
2S = 2 . ( 1 + 2 + 22 + ... + 29 + 210 )
2S = 2 + 22 + 23 + ... + 210 + 211
2S - S = ( 2 + 22 + 23 + ... + 210 + 211 ) - ( 1 + 2 + 22 + ... + 29 + 210 )
S = 211 - 1
S = 1 + 2 + 22 + ... + 29 + 210
2S = 2 . ( 1 + 2 + 22 + ... + 29 + 210 )
2S = 2 + 22 + 23 + ... + 210 + 211
2S - S = ( 2 + 22 + 23 + ... + 210 + 211 ) - ( 1 + 2 + 22 + ... + 29 + 210 )
S = 211 - 1
\(A=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^9}\)
\(2A=2\left(1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^9}\right)\)
\(2A=2+\frac{2}{2}+\frac{2}{2^2}+...+\frac{2}{2^9}\)
\(2A=2+1+\frac{1}{2}+...+\frac{2}{2^8}\)
=>\(A=2+\frac{-1}{29}\)
=>\(A=\frac{57}{29}\)
\(A=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^9}\)
=> \(2A=2+1+\frac{1}{2}+...+\frac{1}{2^8}\)
=> \(A=\left(2+1+\frac{1}{2}+...+\frac{1}{2^8}\right)-\left(1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^9}\right)\)
=> \(A=2+1+\frac{1}{2}+...+\frac{1}{2^8}-1-\frac{1}{2}-\frac{1}{2^2}-...-\frac{1}{2^9}\)
=> \(A=2-\frac{1}{2^9}\)